Optimizing antidotal treatment with the oral HSP90 inhibitor TAS-116 against hydrochloric acid-induced pulmonary fibrosis in mice - Solopov, Pavel A.; Colunga Biancatelli, Ruben Manuel Luciano; Dimitropolou, Christiana; Day, Tierney; Catravas, John D. (Frontiers in Pharmacology, 2022)
Exposure to high concentrations of hydrochloric acid (HCl) can lead to severe acute and chronic lung injury. In the aftermath of accidental spills, victims may be treated for the acute symptoms, but the chronic injury is often overlooked. We have developed a mouse model of acute and chronic lung injury, in which the peak of acute lung injury occurs on the day 4 after HCl exposure. We have also demonstrated that HSP90 inhibitors are effective antidotes when administered starting 24h after HCl. In this study we examined the hypothesis that the novel oral HSP90 inhibitor TAS-116 can effectively ameliorate HCl-induced lung injury even when treatment starts at the peak of the acute injury, as late as 96 hours after HCl. C57BI/6J mice were intratracheally instilled with 0.1N HCl. After 24 or 96 h, TAS-116 treatment began (3.5, 7 or 14 mg/kg, 5 times per week, p.o.) for either 2,3 or 4 or weeks. TAS-116 moderated the HCl-induced alveolar inflammation, as reflected in the reduction of white blood cells and total protein content in bronchoalveolar lavage fluid (BALF), overexpression of NLRP3 inflammasome, and inhibited the activation of pro-fibrotic pathways. Furthermore, TAS-116 normalized lung mechanics and decreased the deposition of extracellular matrix proteins in the lungs of mice exposed to HCl. Delayed and shortened treatment with TAS-116, successfully blocked the adverse chronic effects associated with acute exposure to HCl.